2012
DOI: 10.1128/mmbr.05007-11
|View full text |Cite
|
Sign up to set email alerts
|

The Multiple Signaling Systems Regulating Virulence in Pseudomonas aeruginosa

Abstract: SUMMARY Cell-to-cell communication is a major process that allows bacteria to sense and coordinately react to the fluctuating conditions of the surrounding environment. In several pathogens, this process triggers the production of virulence factors and/or a switch in bacterial lifestyle that is a major determining factor in the outcome and severity of the infection. Understanding how bacteria control these signaling systems is crucial to the development of novel antimicrobial agents capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
637
0
13

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 640 publications
(655 citation statements)
references
References 213 publications
(199 reference statements)
5
637
0
13
Order By: Relevance
“…Among these, proteases can disrupt lung tissue and modulate host inflammatory response [68]; the blue-green pigment pyocyanin causes host cells oxidative stress and dysregulates immune mechanisms [911]; the siderophore pyoverdine is both able to sequester iron from host depots and to regulate bacterial virulence [12,13]. In a previous study, we observed that macrolide antibiotic azithromycin (AZM) acts on P. aeruginosa by reducing the synthesis of proteases and other exoproducts involved in bacterial virulence and the associated host inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, proteases can disrupt lung tissue and modulate host inflammatory response [68]; the blue-green pigment pyocyanin causes host cells oxidative stress and dysregulates immune mechanisms [911]; the siderophore pyoverdine is both able to sequester iron from host depots and to regulate bacterial virulence [12,13]. In a previous study, we observed that macrolide antibiotic azithromycin (AZM) acts on P. aeruginosa by reducing the synthesis of proteases and other exoproducts involved in bacterial virulence and the associated host inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
“…Exceptions to this are species that utilize multiple synthase/receptor pairs that generate and respond to distinct AHL molecules, as is the case for P. aeruginosa (Fig. 1B) (7), as well as species that carry so-called "solo" LuxR-type receptors that have no cognate LuxI-type synthase, such as QscR of P. aeruginosa and SidA of Escherichia coli (33). …”
Section: Ahl-based Quorum Sensingmentioning
confidence: 99%
“…Second, quorum sensing regulates the expression of numerous virulence-related products and has been shown to be important for P. aeruginosa pathogenesis in various model infection systems. Third, this pathogen poses a large burden on the medical community due to its extensive resistance to antibiotics and the current lack of effective treatment options (7), and thus discovery of quorumquenching inhibitors amenable to therapeutic applications would be of high value. Quorum sensing in P. aeruginosa is a complex network comprised of at least three distinct signal/receptor pairs that function in a hierarchical fashion (Fig.…”
Section: Quorum Sensing In the Model Pathogen P Aeruginosamentioning
confidence: 99%
See 2 more Smart Citations